Does Learning Beget Learning Throughout Adulthood? Evidence from Employees' Training Participation - Anica Kramer; Marcus Tamm (Institute for the Study of Labor (IZA), 2016)
Individuals with more years of education generally acquire more training later on in life. Such a relationship may be due to skills learned in early periods increasing returns to educational investments in later periods. This paper addresses the question whether the complementarity between education and training is causal. The identification is based on exogenous variation in years of education due to a reform of the schooling system and the buildup of universities. Results confirm that education has a significant impact on training participation during working life.
Keywords: I21; I24; I26; J24; 330; training; lifelong learning; returns to schooling